Enhancing L2 Speaking Skills Through Small Group Discussion: A Quasi-Experimental Study in Indonesian Secondary Education - Feren Putri Patricia; Said, Mawardin Muhammad; Patmasari, Andi; Marhum, Mochtar (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2024)
This study investigated the effectiveness of Small Group Discussion (SGD) technique in developing English speaking skills among Grade IX students at SMPN 3 Banawa, Indonesia. Through a quasi-experimental design, 49 students were divided into experimental and control groups, focusing on expressions of hope, wishes, and congratulations. The experimental group received SGD treatment over four meetings, while the control group followed conventional teaching methods. Statistical analysis revealed significant improvement in the experimental group’s speaking skills, with mean scores increasing from 38.94 to 71.15. The t-test results (t-counted=3.70462, t-table=2.01174, p<0.05) demonstrated SGD’s effectiveness in enhancing students’ speaking fluency and appropriacy. The findings suggest that SGD creates a supportive learning environment that boosts student confidence and participation in English speaking activities, offering valuable insights for language teaching methodology.